Terror, Fear and Individual and Community Well-Being - Aly, Anne (Springer, 2012)
Fear is often described as an intense human emotion in response to a perceived threat or impending doom. In today’s globalised world where climate change, financial crises and international crime form a new agenda of fear, insecurity and fear have become pervasive forces in the everyday lives of individuals and communities. The terrorist attacks on the United States in 2001 ushered in an era of new fears about international terrorism and new debates about security, civil rights and insecurity. Insecurity became transformed from a situational emotional response to a perpetual state of alertness, and terrorism is imagined as an unknown, but impending, doom: where the everyday has become subliminally associated with the threat of terrorism and the increased security presence invokes the spectre of security and amplifies threat in the public imagination. This chapter will explore the fear of terrorism and its impact on community and individual well-being. It is based on a research project on responses to media discourses on fear among Australian Muslim communities and the broader Australian community. The research incorporated Australia’s first Metric of Fear that measured both community and individual perceptions of safety and security in response to the threat of terrorism. The findings reported here indicate that the fear of terrorism extends beyond an individual fear vis a vis being physically harmed in a terrorist attack. The fear of terrorism is also a community fear associated with perceived threat to civil liberties and democratic freedom. For Australian Muslim communities, the fear of terrorism is very much associated with community identity and their status as a community to be feared.